An evaluation of tests used for the diagnosis and monitoring of C1 inhibitor deficiency: normal serum C4 does not exclude hereditary angio‐oedema - Tarzi, M. D.; Hickey, A.; Förster, T.; Mohammadi, M.; Longhurst, H. J. (Clinical and experimental immunology, 2007)
Summary Reduced levels of serum C4 have been considered a ubiquitous finding in hereditary angio‐oedema (HAE), and consequently low C4 is often used to ‘request manage’ access to C1 inhibitor assays in the United Kingdom. However, in our experience normal C4 may occasionally be compatible with HAE. We audited the results of serum C4, C1 inhibitor antigen (C1inhA) and C1 inhibitor function (C1inhF) in 49 HAE patients, compared to a control group of 58 unaffected subjects. The sensitivity of low serum C4 for HAE among untreated patients was 81%; levels of complement C4 were within the normal range on nine separate occasions in five untreated HAE patients. Molecular genetic analysis of these individuals demonstrated novel mutations in the C1 inhibitor gene. The supplied reference ranges for the Quidel C1inhF enzyme‐linked immunosorbent assay (ELISA) system appear to be too low, with a sensitivity of just 57% for HAE. Following optimization of the reference ranges using receiver operating characteristic analysis, low C1inhF was found to be 78% sensitive and 100% specific for HAE. The diagnosis of HAE is not excluded by normal levels of complement C4. We conclude that C1 inhibitor studies should be performed regardless of serum C4 where a high index of clinical suspicion exists.